(z-5)(z+7)=0

Simple and best practice solution for (z-5)(z+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (z-5)(z+7)=0 equation:


Simplifying
(z + -5)(z + 7) = 0

Reorder the terms:
(-5 + z)(z + 7) = 0

Reorder the terms:
(-5 + z)(7 + z) = 0

Multiply (-5 + z) * (7 + z)
(-5(7 + z) + z(7 + z)) = 0
((7 * -5 + z * -5) + z(7 + z)) = 0
((-35 + -5z) + z(7 + z)) = 0
(-35 + -5z + (7 * z + z * z)) = 0
(-35 + -5z + (7z + z2)) = 0

Combine like terms: -5z + 7z = 2z
(-35 + 2z + z2) = 0

Solving
-35 + 2z + z2 = 0

Solving for variable 'z'.

Factor a trinomial.
(-7 + -1z)(5 + -1z) = 0

Subproblem 1

Set the factor '(-7 + -1z)' equal to zero and attempt to solve: Simplifying -7 + -1z = 0 Solving -7 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1z = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1z = 0 + 7 -1z = 0 + 7 Combine like terms: 0 + 7 = 7 -1z = 7 Divide each side by '-1'. z = -7 Simplifying z = -7

Subproblem 2

Set the factor '(5 + -1z)' equal to zero and attempt to solve: Simplifying 5 + -1z = 0 Solving 5 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1z = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1z = 0 + -5 -1z = 0 + -5 Combine like terms: 0 + -5 = -5 -1z = -5 Divide each side by '-1'. z = 5 Simplifying z = 5

Solution

z = {-7, 5}

See similar equations:

| X^2=128y^2 | | 8t-11=4t+43 | | 40x+24x=544 | | 8b+20=5b-10 | | 2x/3-1=x/3+4 | | 40x+18x=544 | | 3+b=x | | x-11.3=11.4 | | 33t^2-18t+2=0 | | 5x-28+28=7+28 | | x+4(x-7)=7 | | x^2+16x-280=0 | | 5/6x-4 | | 21X+4Y=7000 | | 5x+8=3x+52 | | 22/49*21/52*8/3 | | 315*31/63*23/25 | | 315x31/63x23/25 | | 9-8x=43x+16 | | 132/1*17/4*4/9 | | -54-4=6-10x | | 57-6=8x+13 | | 132*17/4*4/9 | | 3x+7=77-4 | | -7+y=-27 | | -9x-3y=6 | | m^2+7m-51/4=0 | | (X^2+3x+4)=0 | | 4(1+108x)=5 | | (3x+1)(9x^2-4)=0 | | 9b^6+24b^3+16= | | 5x+8y=4y |

Equations solver categories